Evaluasi Program Pendidikan : Pedoman Teoritis Praktis Bagi Praktisi Pendidikan - ARIKUNTO, Suharsimi (Bumi Aksara, 2007)
Evaluasi Program Pendidikan : Pedoman Teoritis Praktis Bagi Praktisi Pendidikan